Purchasing : a guide for hospitality professionals - Hayes, David K.; Ninemeier, Jack D. (Upper Saddle River, New Jersey : Prentice-Hall, 2010)
This textbook contains essential information pertaining to the critical task of effective purchasing for food and beverage operations. Its thirteen chapters are divided into two parts. Part I details effective management procedures to be used from the time the need for a product is identified until product payment is processed and the entire purchasing system is evaluated. Part II presents the specific product information that hospitality purchasers must know as they select food and beverage products, non-food items, capital equipment, and technology.
1. Introduction to Purchasing Management -- 2. Determining Quality Requirements -- 3. Determining Purchase Quantities -- 4. Identifying and Maintaining Supply Sources -- 5. Selecting Suppliers and Ordering Products -- 6. Purchasing Follow-up : Receiving, Storage, Payment, and Evaluation -- 7. Meats, Poultry, and Seafood -- 8. Produce, Dairy, and Eggs -- 9. Groceries -- 10. Beverages -- 11. Buying Nonfood Items -- 12. Buying Technology and Services -- 13. Purchasing Capital Equipment.
Includes index.
Keywords: PURCHASING -- MANAGEMENT